2014
DOI: 10.4097/kjae.2014.66.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milrinone on the inflammatory response and NF-kB activation in renal ischemia-reperfusion injury in mice

Abstract: BackgroundMilrinone increases intracellular adenosine 3',5'-cyclic monophosphate concentration and enhances vascular relaxation. Nuclear factor-kappa B (NF-kB) plays a key role in inflammatory responses during ischemia-reperfusion (I/R) injury. We aimed to investigate the effect of milrinone on the inflammatory responses and NF-kB activation in renal I/R injury in mice.MethodsThirty C57BL/6 mice were allocated into 3 groups. In group S (n = 10), only right nephrectomy was done. In group C (n = 10), the left ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In 2004, Cao and colleagues reported that transfection of NF-κB decoy oligodeoxynucleotides abolished NF-κB activation in ischemic AKI, resulting in decreases in MCP-1 and ICAM-1 expression, suppression of monocyte/ macrophage infiltration, and significant attenuation of tissue damage (Cao et al, 2004). Consistently, NF-κB activation was inhibited by pharmacologic agents such as milrinone and resveratrol or overexpression of SIRT1, resulting in a better preservation of renal histology and function in ischemic-AKI and cisplatin nephrotoxic (Jung et al, 2014; Jung et al, 2012). Blockade of NF-κB was also implicated in the protective effect of Nrf2 signaling (Jiang et al, 2014).…”
Section: Agents Targeting Gene Expressionmentioning
confidence: 86%
“…In 2004, Cao and colleagues reported that transfection of NF-κB decoy oligodeoxynucleotides abolished NF-κB activation in ischemic AKI, resulting in decreases in MCP-1 and ICAM-1 expression, suppression of monocyte/ macrophage infiltration, and significant attenuation of tissue damage (Cao et al, 2004). Consistently, NF-κB activation was inhibited by pharmacologic agents such as milrinone and resveratrol or overexpression of SIRT1, resulting in a better preservation of renal histology and function in ischemic-AKI and cisplatin nephrotoxic (Jung et al, 2014; Jung et al, 2012). Blockade of NF-κB was also implicated in the protective effect of Nrf2 signaling (Jiang et al, 2014).…”
Section: Agents Targeting Gene Expressionmentioning
confidence: 86%
“…Data are presented as the mean ± SD. # P < 0.01 versus the sham group; *P < 0.01 versus the vehicle group enzymes, and cytokines, such as TNF-α, IL-1β, and IL-6, to initiate inflammatory responses [31]. A previous study reported that the inhibition of NF-κB signaling is neuroprotective because it reduces infarct size, improves neurological deficits, and leads to the inhibition of the expression of inflammatory response genes [32], suggesting that targeting NF-κB activity after acute cerebral infarction may be a potential therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that NF-κB plays a strong role in the initiation of inflammatory responses [39-41]. Recently, RIPK3, the critical biomarker for necroptosis, was shown to facilitate inflammation through NF-κB [26, 42].…”
Section: Discussionmentioning
confidence: 99%